POTENSI BUAH MENGKUDU (Morinda citrifolia L.) SEBAGAI ANTI RADANG PADA LUKA GORES MENCIT JANTAN (Morinda citrifolia L. Fruit Potency as Anti Inflamatory in Male Mice Scratch) - Kamalia Fikri (Saintifika, 2015)
Morinda citrifolia L. is known commercially as mengkudu, grows widely throughout in Indonesia and is one of the most significant sources of traditional medicines. In fact, mengkudu contains a very important alkaloids, xeronine. This alkaloid helps in the normalization of abnormally functioning cells. This research aims is to knowing the influence of Morinda citrifolia L. fruit to the number of neutrophil cell in male mice scratch wound. There was 6 group as a treatment group, in which every group contain 4 mice. Every group had different time in neutrophil cell observation, it was 12, 24, 36, 48, 60 and 72 hour/ observation. The result showed that the number of neutrophil cell tend to decrease. And based on LSD test the number of neutrophil cell different signicantly in 48 hour of observation.